2010
DOI: 10.1186/1471-2407-10-688
|View full text |Cite
|
Sign up to set email alerts
|

Tumor location and patient characteristics of colon and rectal adenocarcinomas in relation to survival and TNM classes

Abstract: BackgroundOld age at diagnosis is associated with poor survival in colorectal cancer (CRC) for unknown reasons. Recent data show that colonoscopy is efficient in preventing left-sided cancers only. We examine the association of Tumor Node Metastasis (TNM) classes with diagnostic age and patient characteristics.MethodsThe Swedish Family-Cancer Database has data on TNM classes on 6,105 CRC adenocarcinoma patients. Ordinal logistic regression analysis was performed to model tumor characteristics according to age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 27 publications
8
57
2
4
Order By: Relevance
“…Registry-based studies in Sweden and Japan suggested the majority of cancers in people with a family history were distally located. 33,36 However, two other studies found a more even distribution of distally and proximally located cancers. 32,34 In three studies providing data on stage at diagnosis by family history, there was no evidence of differential distributions of stage in people with a family history of CRC compared to those without.…”
Section: Resultsmentioning
confidence: 95%
“…Registry-based studies in Sweden and Japan suggested the majority of cancers in people with a family history were distally located. 33,36 However, two other studies found a more even distribution of distally and proximally located cancers. 32,34 In three studies providing data on stage at diagnosis by family history, there was no evidence of differential distributions of stage in people with a family history of CRC compared to those without.…”
Section: Resultsmentioning
confidence: 95%
“…Kroman et al demonstrated that the clinical survival is significantly better for patients with a tumor in the upper lateral quadrant than that located elsewhere in the breast [36]. Hemminki et al reported that tumor location of colorectal cancer was closely related to TNM classes and survival [37]. Conversely, Li et al demonstrated that tumor location cannot be used to predict oncologic outcomes in patients with primary ureteral urothelial carcinoma [38].…”
Section: Discussionmentioning
confidence: 99%
“…Such a misclassification might lead to a ‘reverse causal’ relationship biasing the unadjusted observation toward the null. The effect on survival may be more pronounced for rectal cancers because patients are aware of symptoms at an earlier stage than for colonic cancers 24. The induction period of smoking on colorectal cancer is usually at least 30 years and this may explain why former smokers remained at increased risk.…”
Section: Discussionmentioning
confidence: 99%